2021
DOI: 10.1166/jmihi.2021.3699
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Motor Nerve Function Rehabilitation in Patients with Upper Extremity Hemiplegia Based on Functional Magnetic Resonance Imaging

Abstract: Through functional magnetic resonance imaging (fMRI) technology, it is planned to use complex brain network technology to track brain functional imaging tracking treatment of stroke hemiplegia with scalp acupuncture. Functional magnetic resonance imaging (fMRI) can continuously monitor the rehabilitation process of motor nerve function in patients with stroke and upper limb hemiplegia, and explore the mechanism of brain plasticity changes at different levels of neural function cortex, motor function neural ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In sports physiology, there is a phenomenon of cross-migration of training effects, which means that unilateral limb movement can produce simultaneous improvement in the functions of opposite homologous parts (strength, joint range of motion, function)[ 2 ]. Short, high-intensity resistance exercises on one side of a healthy person's limb can cause the strength of the untrained limb on the opposite side to increase[ 3 ]. It has been found that training the opposite arm can offset muscle atrophy caused by limb fixation, and the phenomenon of cross-migration is unilateral, which can only be transferred from the dominant limb to the non-dominant limb[ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In sports physiology, there is a phenomenon of cross-migration of training effects, which means that unilateral limb movement can produce simultaneous improvement in the functions of opposite homologous parts (strength, joint range of motion, function)[ 2 ]. Short, high-intensity resistance exercises on one side of a healthy person's limb can cause the strength of the untrained limb on the opposite side to increase[ 3 ]. It has been found that training the opposite arm can offset muscle atrophy caused by limb fixation, and the phenomenon of cross-migration is unilateral, which can only be transferred from the dominant limb to the non-dominant limb[ 4 ].…”
Section: Introductionmentioning
confidence: 99%